LEAD (Pb)-INHIBITED EARLY ROOT GROWTH IN WHEAT INVOLVES ALTERATIONS IN ASSOCIATED BIOCHEMICAL PROCESSES - KAUR, GURPREET; SINGH, HARMINDER PAL; DAIZY R. BATISH; RAVINDER KUMAR KOHLI (The Bioscan, 2010)
The present study investigated the effect of Lead (Pb; 50 and 500 μM) on biochemical alterations during the early radicle growth. It was observed that Pb-exposure significantly enhanced the contents of water-soluble proteins and carbohydrates in wheat radicle after 24 h in a dose-response manner. Proteins and carbohydrates content increased by 2.3- and 3.5-folds, respectively at 500 μM Pb-exposure. On the other hand, the activities of hydrolyzing enzymes proteases and amylases were drastically reduced. At 500 μM, activities of proteases, α-amylases, and β−amylases decreased by 92, 55, and 82% respectively. In addition, Pb-exposures significantly enhanced the activities of enzymes - peroxidases, polyphenol oxidases by 2.6- and 2.2- times, respectively, over of control at 500μM Pb. Enhancement in the activities of these enzymes indicate their upregulation / induction in response to Pb-induced toxicity in wheat radicle and provide protection. The study concludes that Pb-induced toxicity in emerging wheat seedlings involves the biochemical alterations in terms of macromolecules and the activities of related enzymes to cope with the Pb-stress.